ANTIBACTERIAL ACTIVITIES OF CHITOSAN IN HARUAN FISH SCALES (Channa striata) TO THE GROWTH OF Staphylococcus aureus - Dewi Retno Wahyu Widyaningrum; Deby Kania Tri Putri; Irham Taufiqurrahman (FKG Unlam, 2019)
Background: Haruan fish scales (Channa striata) contain chitin which can be used as antibacterial ingredients by processing it into chitosan. Chitosan contains an amino polysaccharide group which can inhibit the growth of Staphylococcus aureus, one of the opportunistic bacteria, which becomes a pathogen if there is an imbalance within oral environment and one of the causes of periodontal disease. Besides, these bacteria are also reported to be resistant to conventional antibacterial agents. Objective: The purpose of this study was to find out and elaborate the difference in antibacterial activity of chitosan from haruan fish scales (Channa striata) at the concentration of 0.5%; 1%; 1.5%; 2%; 2.5%; 3%; 3.5%; 4% on the growth of Staphylococcus aureus. Methods: This study used a randomized pretest-posttest with control group design and One Way ANOVA statistical test was performed and was followed by Post Hoc Dunnet test. The procedure of this study consisted of chitosan fabrication scales from fresh fish by deproteination, demineralization, and deacetylation, followed by an anti-bacterial test with 10 treatment groups namely 0.5%; 1%; 1.5%; 2%; 2.5%; 3%; 3.5%; 4% on the growth of Staphylococcus aureus to obtain Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Results: The results of this study presented chitosan at 1.5% concentration as the Minimum Inhibitory Concentration (MIC) and 3.5% concentration as the Minimum Bactericidal Concentration (MBC) on the growth of Staphylococcus aureus. Evaluated from the difference in absorbance, 2.5% chitosan concentration showed superior activity in inhibiting Staphylococcus aureus compared to 0.2% chlorhexidine gluconate. Conclusion: It can be concluded that there are differences in the antibacterial activity of chitosan scales (Channa striata) with a concentration of 0, 5%; 1%; 1.5%; 2%; 2.5%; 3%; 3.5%; 4% on the growth of Staphylococcus aureus.